High-Fat Diet Causes Subfertility and Compromised Ovarian Function Independent of Obesity in Mice. Issue 9 (September 2016) - Skaznik-Wikiel, Malgorzata E.; Swindle, Delaney C.; Allshouse, Amanda A.; Polotsky, Alex J.; McManaman, James L.
Abstract : (Abstracted from Biol Reprod 2016;94(5):108) Obesity, caused by excess calorie consumption and high-fat diet (HFD), is a condition that is highly prevalent in developing countries, estimated to affect approximately 41% of the population by the end of 2015. A common problem in women, obesity is associated with multiple reproductive affects such as anovulation, irregular menses, infertility, miscarriage, and adverse pregnancy outcomes with assisted and spontaneous conceptions.